Fear of hypoglycemia and its association with well-being, metabolic outcomes, and psychological health: A cross-sectional study in Danish adolescents with type 1 diabetes - Amalie Hundahl; Louise Norman Jespersen; Stine Møller Sildorf; Emilie Bundgaard Lindkvist; Karl Bang Christensen; Steffen Ullitz Thorsen; Jannet Svensson (PLoS ONE, 2025)
Introduction Fear of hypoglycemia (FoH) among adolescents with type 1 diabetes (T1D) may hinder optimal diabetes treatment. This study aimed to investigate the association between FoH and metabolic outcome and psychological health. Materials and methods Adolescents aged 11–18 with T1D and their parents were recruited from a diabetes clinic in Copenhagen from 2016–2017. Data were collected from 142 adolescents and 123 parents using Children’s Hypoglycemia Index (CHI), the World Health Organization-Five Well-Being Index, the Adherence in Diabetes Questionnaire, and DISABKIDS (health-related quality of life). Associations between CHI scores and clinical, demographic, and psychological data were analyzed. Rasch modeling was used for psychometric validation of Danish version of CHI. Results Higher CHI scores were observed in females (p = 0.01). Adolescent and parental CHI scores were significantly correlated across CHI subscales (r = 0.20–0.33). With increasing CHI scores, we observed a decrease in well-being (p = 0.004), and health-related quality of life (p=<0.0001–0.007). No associations were found with HbA1c, treatment methods, blood glucose monitoring, diabetes duration, or adherence (p = 0.06). The Danish version of the CHI proved valid and useful for detecting FoH. We found an acceptable fit to the Rasch model across all three subscales. Conclusion Though not related directly to treatment outcome FoH might be an important indicator of psychological health in adolescents with T1D.